Development of Student Worksheets to Improve Students’ Science Literacy on Amphibian Material - Silmi Fadhila Ihsani; Epa Paujiah; Tri Wahyu Agustina; Tri Cahyanto (FKIP - Universitas Riau, 2026)
This study aimed to develop a science literacy based Student Worksheets on amphibian material to improve students’ science literacy. The research employed a Research and Development (R&D) method using the 3D model consisting of Define, Design, and Develop stages. The study was conducted at one of the schools in Bandung district involving 40 tenth grade students selected through random sampling. Data were collected through interviews, observations, validation questionnaires, and science literacy tests in the form of pretest and posttest. The worksheets was validated by material expert, pedagogical expert, and biology teacher, obtaining validity scores of 61.33%, 90.67%, and 92%, respectively. Based on material expert feedback, revisions were made to improve content accuracy, align science literacy indicators with learning objectives, and clarify learning activities before implementation. The revised worksheets was categorized as valid and highly valid for classroom use. The effectiveness test showed an increase in students’ science literacy, with the average score rising from 39 on the pretest to 77 on the post test. The N-Gain score of 0.59 was categorized as moderate. These findings indicate that the developed worksheets is feasible and effective in supporting biology learning and improving student science literacy.